Mutu Pelayanan Sebagai Determinan Kepuasan Dan Loyalitas Pasien Rumah Sakit - Ahmad Murtadho; Sumarji Sumarji (Universitas Islam Kadiri, 2020)
The effect of service quality to satisfaction and loyalty of outpatiens Rumah Sakit Bhayangkara Nganjuk. The aim of this study are : 1) To know the effect of service quality to satisfaction of the outpatients Rumah Sakit Bhayangkara Nganjuk, 2) To know the effect of service quality to loyalty of the outpatients Rumah Sakit Bhayangkara Nganjuk, 3) To know the effect of service quality to satisfaction and loyalty of the outpatients Rumah Sakit Bhayangkara Nganjuk. There were 150 respondents in these research within their criteria has passing senior high school degree and more than two times taking outpatient or accompanying outopatient's at Rumah Sakit Bhayangkara Nganjuk. The sample deciding method is purposive sampling. To gain the result as the researchgoal, structural equation modelling SEM were analyzed by analysis moment of structure (AMOS) and special package for statistic science (SPSS). The results shows that : 1) Service quality positive and significantly effects the satisfaction of the outpatient Rumah Sakit Bhayangkara Nganjuk, 2) Service quality positive and significantly effects the loyalty of the outpatient Rumah Sakit Bhayangkara Nganjuk and 3) Service Quality positive and significanty effects the satisfaction and loyalty of the outpatient Rumah Sakit Bhayangkara Nganjuk.